Steel metallurgy : properties, specifications and applications - Mondal, S. K. (New York : Mcgraw-Hill Education, 2015)
This highly illustrated resource covers the characteristics, properties, specifications, heat treatment, and application of steels for engineering students, non-metallurgical engineers, and technicians. There's a saying that "steel makes the world." From a tiny pin in a sewing kit to home appliances to cars to bridges, steel is everywhere. While there are numerous books on steel, few, if any, address the true application of steels in a practical manner. This book was written to fill that gap. Divided into four parts, Steel Metallurgy: Properties, Specifications, and Applications covers the basic metallurgical facts and characteristics, properties, standards, and grades of steel. Classifications of steel based on standards and structural engineering are then discussed, followed by heat treatment and welding of steels. The book then focuses on the application of steel and its reliability and failures, and shows, through numerous illustrations and case studies, how it's processed and used for various purposes. Armed with the information in this book, metallurgical and engineering students will become truly "industry ready." Case studies and illustrations show steel being used in practical, everyday applications, making the book user friendly yet comprehensive Lays the ground work for steel selection, and discusses the methods of selection Contains appendices with steel grades, compositions, and standards; physical data and conversions; temperature, hardness, and work/energy conversion tables Includes a glossary of important metallurgical terms
Ch. 1 Introduction to Steel: Metallurgical Characteristics and Properties Ch. 2 Formation of Microstructures in Steel: Structure/Property Relationship Ch. 3 Influence of Grain Size and Inclusions on the Properties of Steels Ch. 4 Steelmaking and Rolling for Quality Steel Production Ch. 5 Types of Steel Properties and Their EvaluationCh. 6 Classification and Specification of Steels: Purpose, Practice, and Role Ch. 7 Properties and Grades of Steels: Structural, Engineering and Stainless Steels Ch. 8 Heat Treatment and Welding of Steels Ch. 9 Selection and Application of Steel: Role of Quality, Cost and Failure Analysis Ch. 10 Selection and Application of Steels: Case StudiesStructural and Flat Product Steels: Engineering Structures; LPG Cylinder; Automotive Wheel Rims; Automobile Body Parts Engineering and Long Product Steels: Automotive Axle Shafts; Pivot Pins; Fastening Bolts; Ball Bearings Appendices Glossary
Includes bibliographical references and index.
Keywords: Steel -- Metallurgy; Metals technology